ON THE NATURE OF THE TELESEISMIC PN PHASE OBSERVED ON THE ULTRALONG-RANGE PROFILE 'QUARTZ,' RUSSIA - Morozov I.B.; Morozova E.A.; Smithson S.B.; Solodilov L.N. (My University, 1998)
The most prominent secondary phase observed in the records from the ultralong profile "Quartz" crossing northern Eurasia is the high-frequency long-range (teleseismic) P(n). This phase, propagating with the group velocity of about 8.1 to 8.2 km/sec to over 3000 km distances, dominates the records within the frequency range above about 5 Hz. Within this teleseismic P(n), we distinguish onsets of several branches having higher apparent velocities between 8.5 and 8.6 km/sec. Using traveltime modeling techniques, we associate the teleseismic P(n) with whispering gallery modes traveling within the top 160 km of the mantle. The long incoherent coda of this phase results from scattering and from reverberations of seismic waves within the crust. The contrast in frequency contents between the teleseismic P(n), and deeper refracted and reflected phases is explained by the increase of inelastic attenuation within the prominent low-velocity zone (LVZ) below the depth of about 150 km.